2018
DOI: 10.1159/000492427
|View full text |Cite
|
Sign up to set email alerts
|

R Open Source Programming Code for Calculation of the Kidney Donor Profile Index and Kidney Donor Risk Index

Abstract: Background: The Kidney Donor Profile Index (KDPI) and Kidney Donor Risk Index (KDRI) were developed by the United States Organ Procurement and Transplantation Network (OPTN). They may influence the clinical decision whether to accept or discard a donor kidney, but still there are debates about KDPI/KDRI applicability and its consequences. To further evaluate these indexes in different populations, more data should be analyzed, and a universally applicable program code would facilitate it. Currently, KDPI/KDRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…ECD was defined using United Network for Organ Sharing definition [15]. Kidney Donor Profile Index (KDPI) [16] was calculated using "ktx.kdpi.optn," an R open source programming code [17]. tAR included all episodes of acute allograft dysfunction, treated with methylprednisolone and/or rabbit antithymocyte globulin (rATG), regardless of biopsy.…”
Section: Definitionsmentioning
confidence: 99%
“…ECD was defined using United Network for Organ Sharing definition [15]. Kidney Donor Profile Index (KDPI) [16] was calculated using "ktx.kdpi.optn," an R open source programming code [17]. tAR included all episodes of acute allograft dysfunction, treated with methylprednisolone and/or rabbit antithymocyte globulin (rATG), regardless of biopsy.…”
Section: Definitionsmentioning
confidence: 99%
“…a Expressed as difference of means, difference in medians, or difference in proportions as appropriate. b Calculated with the OPTN, mapping coefficients for the 2017 year by kidney.epi R package [24].…”
Section: Discussionmentioning
confidence: 99%
“…A two-sided p value of less than 0.05 was considered statistically significant. The analyses were performed with R version 3.5.2 (R Foundation, Vienna, Austria) using the survival [21], epitools [22], mice [21], nephro [23], and kidney.epi [24] packages, and with STATA version 15 for longitudinal GFR data.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Moreover, a history of diabetes enjoys a higher score than the absence of such a history. [ 25 26 30 ] It is suggested that if a country or a group of researchers want to create a new model, they must study the different models of different countries and consider their differences and create their own native model.…”
Section: Discussionmentioning
confidence: 99%